2019
DOI: 10.15243/jdmlm.2019.062.1617
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of indigenous free nitrogen-fixing bacteria from rhizosphere of Vigna radiata for agricultural land treatment

Abstract: Nitrogen is the most abundant element in the atmosphere, however, most often deficient in agricultural lands. This research was an exploratory to get indigenous non-symbiotic nitrogen-fixing bacteria. Soil samples were collected from rhizosphere of green beans. This study was aimed to determine the bacterial population of the three regions; screening, isolation and selection of free nitrogen-fixing bacteria. Antagonism and pathogenicity tests were performed to observe its potential for a biofertilizer product.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
7
0
5
Order By: Relevance
“…Kuan et al (2016) noted that almost 80% of the N available to plants comes from the symbiotic group, including Rhizobium which infects plants to form nodules. Whereas the nonsymbiotic group consists of free-living microorganisms, such as, Bacillus, Azotobacter, Azospirillum, and Herbaspirillum (Arfarita et al, 2019), which contributes to approximately 5-10% of the biological N inputs into the soil N cycle (Son, 2001). In a two-year field study, Amirnia et al (2019) demonstrated that N 2 -fixing bacterial strain belonging to the genus of Azotobacter in combination with AMF (Glomus intraradices) enhanced soil fertility and plant growth under rainfed conditions, as application resulted in higher biomass yield, seed yield and seed protein of lentil (Lens culinaris Medik), thus the authors suggested that this bio-fertilizer has great potential in an arid and semi-arid area, in order to fulfill plant nitrogenous requirements and productivity under rainfed conditions.…”
Section: Nitrogen-fixing Bacteria and Phosphate Solubilizing Microorgmentioning
confidence: 99%
“…Kuan et al (2016) noted that almost 80% of the N available to plants comes from the symbiotic group, including Rhizobium which infects plants to form nodules. Whereas the nonsymbiotic group consists of free-living microorganisms, such as, Bacillus, Azotobacter, Azospirillum, and Herbaspirillum (Arfarita et al, 2019), which contributes to approximately 5-10% of the biological N inputs into the soil N cycle (Son, 2001). In a two-year field study, Amirnia et al (2019) demonstrated that N 2 -fixing bacterial strain belonging to the genus of Azotobacter in combination with AMF (Glomus intraradices) enhanced soil fertility and plant growth under rainfed conditions, as application resulted in higher biomass yield, seed yield and seed protein of lentil (Lens culinaris Medik), thus the authors suggested that this bio-fertilizer has great potential in an arid and semi-arid area, in order to fulfill plant nitrogenous requirements and productivity under rainfed conditions.…”
Section: Nitrogen-fixing Bacteria and Phosphate Solubilizing Microorgmentioning
confidence: 99%
“…Dari penelitian tersebut didapat bakteri indigenus yang terdiri dari 3 bakteri tanah antara lain bakteri penambat N free Bacillus cereus, bakteri pelarut fosfat Pantoea ananatis dan bakteri penghasil EPS (eksopolisakarida) Pseudomonas plecoglossicida. Arfarita, et al, (2019) telah melakukan penelitian tentang eksploitasi bakteri pengikat nitrogen bebas dari rizosfer tanaman kacang hijau untuk pengolahan lahan pertanian.…”
Section: Pendahuluanunclassified
“…The used of vermiwash was expected not only to support the microbe viability but also serve as carrier material that is important in manufacturing the biofertiizer. In this study, the bacteria used as inoculants are indigenous bacteria from various place such as : Junrejo in Batu region and two site in Malang region which are Kendalpayak and Jambe Gede, namely : free Nitrogen (N) fixing bacteria (Bacillus licheniformis), soluble Phosphate (P) bacteria (Pantoea ananatis) and Exopolysaccharide (EPS) producing bacteria (Pseudomonas plecoglossicida) obtained from previous studies (Arfarita, Muhibuddin, & Imai, 2019). The information related with the compatibility of the carrier material with the respected microbes, the self life and their pathogenicity are still limited.…”
Section: Introductionmentioning
confidence: 99%